1996
DOI: 10.1210/en.137.2.622
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine-induced cFos expression in the hypothalamic paraventricular nucleus is dependent on brainstem effects: correlations with cFos in catecholaminergic and noncatecholaminergic neurons in the nucleus tractus solitarius

Abstract: Systemically administered nicotine elicits ACTH release indirectly by acting on neurons in brainstem catecholaminergic regions known to send afferent projections to the paraventricular nucleus of the hypothalamus (PVN), the site of CRH neurons involved in initiating ACTH secretion. The present study in rats examined 1) the relationship between dose-dependent expression of cFos in the PVN and that in the nucleus of the solitary tract (NTS)-A2, NTS-C2 and locus coeruleus (LC), after iv nicotine (0.045-0.18 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 0 publications
2
27
0
1
Order By: Relevance
“…Acute nicotine elevates Fos expression in various brain regions, including dopaminergic target areas (Ren and Sagar, 1992;Matta et al, 1993;Pang et al, 1993;Kiba and Jayaraman, 1994;Panagis et al, 1996;Salminen et al, 1996;Valentine et al, 1996). In the present study, GTS decreased nicotine-induced Fos protein expression in the nucleus accumbens and striatum.…”
Section: Discussionsupporting
confidence: 61%
“…Acute nicotine elevates Fos expression in various brain regions, including dopaminergic target areas (Ren and Sagar, 1992;Matta et al, 1993;Pang et al, 1993;Kiba and Jayaraman, 1994;Panagis et al, 1996;Salminen et al, 1996;Valentine et al, 1996). In the present study, GTS decreased nicotine-induced Fos protein expression in the nucleus accumbens and striatum.…”
Section: Discussionsupporting
confidence: 61%
“…Acute nicotine activated CRF ϩ neurons in adult rat PVN (Valentine et al, 1996;Loughlin et al, 2006) but did not change their number (Loughlin et al, 2006). Additionally, nicotine increased CRF mRNA in an immortalized amygdala cell line (Kasckow et al, 1999), hypothalamic CRF-like immunoreactivity was increased in adult rats exposed to nicotine during adolescence (Slawecki et al, 2005), and hypothalamic provasopressin mRNA increased on day 1-4 of daily nicotine injection (Hollt and Horn, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…In animals, acute injection of nicotine, the principal psychoactive component of tobacco smoke, is a potent stimulus for secretion of the stress-responsive hypothalamo-pituitary-adrenal (HPA) axis hormones ACTH (Conte-Devolx et al, 1981;Cam and Bassett, 1983;Matta et al, 1987) and corticosterone (Balfour et al, 1975;Cam and Bassett, 1983). Acutely injected nicotine increased glutamate release and enhanced NMDA receptor activity in noradrenergic regions of the nucleus tractus solitarius projecting to the hypothalamic paraventricular nucleus (PVN) (Zhao et al, 2007), projections shown to stimulate norepinephrine release and activate corticotropin-releasing factor (CRF) neurons in PVN (Valentine et al, 1996;Matta et al, 1998). However, the effect of chronically self-administered nicotine on these stress-responsive systems has not been fully resolved.…”
Section: Introductionmentioning
confidence: 99%
“…Because previous experiments from our laboratory have shown that a majority of NTS neurons expressing c-Fos in response to i.v. nicotine were not catecholaminergic (Valentine et al, 1996), the phenotype of NTS neurons activated by nicotine remains largely unidentified. It is probable that many of these neurons express NMDA receptors and respond to the glutamate released by nicotine, in turn secreting an unknown neurotransmitter(s) that would account for the NMDA receptordependent, NO-independent fraction (i.e., 20%) of NE released in PVN and AMYG by systemic nicotine.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that nicotine administered into the fourth cerebroventricle or by way of an i.v. infusion stimulates NE release and c-Fos expression in the pcPVN (Valentine et al, 1996;Matta et al, 1998). These are dosedependently correlated with nicotine-stimulated ACTH secretion, largely through recruitment of the noradrenergic system projecting from the NTS-A2 region to pcPVN (Matta et al, 1993b;Fu et al, 1997).…”
mentioning
confidence: 93%